Systematic and Random Mapping Errors in Structure – Function Analysis of the Macula - Montesano, Giovanni (Transl Vis Sci Technol, 2021)
PURPOSE: Quantify the spatial error in mapping perimetric stimuli for structure–function analysis resulting from the choice of mapping scheme and eye movements. METHODS: We analyzed data from 17 healthy and 30 glaucomatous participants. Structural data of the macula were collected with a spectral-domain optical coherence tomography. We extracted eye movement data and projection locations from a fundus tracking perimeter and quantified the retinal location mapping error (distance between the actual and the intended stimulus location in degrees from the fovea) for non-tracked perimetry in a 10-2 grid. First, we evaluated whether rotating the 10-2 grid to match the fovea–disc axis improved mapping accuracy. Second, we analyzed the effect of eccentric fixation, random eye movements, and gaze attraction from seen stimuli on projection accuracy and spread of fixation, measured with the 95% bivariate contour ellipse area (95% BCEA). We used generalized linear mixed models for our statistical analyses. RESULTS: Rotating the 10-2 grid to match the fovea–disc axis significantly increased the mapping error (P < 0.001). Eye movements evoked by seen stimuli significantly increased the projection error during the test (P < 0.001). Removing such eye movements significantly reduced the 95% BCEA (P < 0.001). Eccentric fixation also significantly contributed to the projection error (P < 0.001), and its effect was larger in glaucoma patients (P < 0.001). CONCLUSIONS: Rotating the perimetric grid to match the fovea–disc axis is not recommended. Fixation eccentricity and instability should be taken into account for structure–function analyses. TRANSLATIONAL RELEVANCE: Accounting for fixation can improve structure–function mapping in glaucoma.